Effect of landscape structure on common vole (Microtus arvalis) distribution and abundance at several space scales - Delattre, Pierre; Giraudoux, Patrick; Baudry, Jacques; Quéré, J.P.; Fichet, E. (HAL CCSD, 1996)
International audience